Pengaruh Inovasi Produk Dan Kualitas Produk Terhadap Keunggulan Bersaing Pada Coffee Shop Di Kota Serang Banten - Novita, Andrea; Mukhsin, Moh; Satyanegara, Diqbal (Tirtayasa Ekonomika, 2024)
This research was conducted to determine the influence of Product Innovation and Product Quality on Competitive Advantage at Coffee Shops in Serang City. The method used in this research is quantitative research with a type of causal research. The population and sample in this study used the Slovin technique (Sugiyono, 2017) with a predetermined formula and a calculated sample size of 58 respondents. The data analysis technique in this research uses the SmartPLS 3.3.3 analysis tool. The results of this research show that: (1) Product innovation has a positive and significant effect on competitive advantage in coffee shops. (2) Product quality has an positive and significant effect on competitive advantage in coffee shops.